Analisis Implementasi Pencatatan Keuangan Sederhana dalam Mendukung Digitalisasi UMKM Lokal - Febri Andany; Masyhuri, Masyhuri (Journal of Economic and Business Advancement, 2026)
Micro, small, and medium enterprises (MSMEs) play a strategic role in strengthening local economic resilience, employment generation, and community welfare. This study aims to analyze the implementation of simple financial recording in supporting the digitalization of local MSMEs through a non-empirical approach using library research methods. Data were obtained from scientific articles, proceedings, and recent academic publications related to financial recording, digital accounting, MSME digitalization, and financial literacy. The findings indicate that simple financial recording serves as a fundamental administrative framework that facilitates digital transformation within MSMEs. Implementation effectiveness remains influenced by digital literacy, human resource readiness, organizational adaptability, infrastructure availability, and continuous mentoring support. The study highlights that integrating financial recording with digital technology contributes significantly to MSME sustainability, governance strengthening, and long-term competitive capacity within the evolving digital economy.